Factors of medication non-adherence among type 2 diabetes mellitus patients in Malaysian public hospitals - Nor Fadhilah Abdullah
The prevalence of medications non-adherence (MNA) among type 2 diabetes mellitus (T2DM) patients is high, despite the importance of medications as one of the primary treatments T2DM. The aim of this study is to explore factors of medication non-adherence among T2DM non-adherence patients. This study was a triangulation mixed methods design study conducted among T2DM patients in two hospitals in Klang Valley, Malaysia. A quantitative study involved 427 T2DM patients who were recruited using systematic sampling. A total of 12 participants then participated in qualitative study through a purposive sampling of non-adherence patients revealed from a quantitative study. The Medication Compliance Questionnaire (MCQ) was used to collect information on socio-demography, clinical profiles and non-adherence to medications. Then, semi-structured in-depth interviews have been conducted to explore factors of medication non-adherence among non-adherence type 2 diabetes patients. Descriptive, bivariate and multivariate analysis was performed using the Statistical Package for Social Science (SPSS 23). The interviews were audio-taped and transcribed verbatim. The data were managed using NVivo11 and analyzed using constant comparative analysis. The response rate for this study was 93.4%. Most of the respondents were married (82.0%) and having dyslipidemia (81.7%). A total of 186 (46.6%) of the respondents were not adherence to the medication. Ethnicity, marital status and Haemoglobin A1c (HbA1c) reading have been significantly related with medication non-adherence. Multivariate logistic regression indicated that Malay, with a single, widow, widower or divorces status and poor HbA1c reading, was more likely to become non-adherence. Five categories evolved from participants? response to MNA factors. The first factor was perceived benefit complementary and alternative medicine (CAM). The second factor was attitude towards drawback of limitation. Third factor was poor health care provider-patient relationship. The fourth factor was an undesirable emotional response to the intake of medications. The last factor was the restraint of daily routine and cognitive function. In summary, the prevalence of MNA in this study was unsatisfactory and there is a lot of room for improvement. The patients? information on the socio-demographic and clinical profiles should be considered in future intervention in improving MNA. The design of mixed methods in this study allowed the identification of non-adherence patients. The exploration of factors that influence patients MNA is a key to recommend patient-centred care strategy to improve T2DM patients? non-adherence, which may be a reference for healthcare providers, primarily the nurses to be implemented in improving patients MNA.